2015
DOI: 10.1002/2015ja021522
|View full text |Cite
|
Sign up to set email alerts
|

Dawn‐dusk asymmetry in bursty hot electron enhancements in the midtail magnetosheath

Abstract: Bursty (a few minutes) enhancements of hot electrons (1–10 keV) in the tail magnetosheath, which we name hot electron enhancements (HEEs), are sometimes observed. To understand the processes leading to HEEs, we have used 4 years of measurements from Acceleration Reconnection Turbulence and Electrodynamics of Moon's Interaction with the Sun mission to statistically investigate the dawn‐dusk asymmetry of HEEs in the midtail (x from −30 to −70 RE) magnetosheath and their correlations with the solar wind/interplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…As shown in Figure , a HEE was observed by P2 within the low‐density core at the time when P1 observed the outward intruding magnetosphere, and the electron fluxes within the HEE at >0.5 keV were comparable to the fluxes of the magnetospheric electrons. In addition, statistically HEEs were observed dominantly in the dawnside magnetosheath and when the solar wind speed is higher (Wang et al, ; Wang, Xing, et al, ). This dawn‐dusk asymmetry is consistent with the DD‐related foreshock perturbations being produced on the side of quasi‐parallel shock, which is more often on the dawnside because of the Parker spiral IMF.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure , a HEE was observed by P2 within the low‐density core at the time when P1 observed the outward intruding magnetosphere, and the electron fluxes within the HEE at >0.5 keV were comparable to the fluxes of the magnetospheric electrons. In addition, statistically HEEs were observed dominantly in the dawnside magnetosheath and when the solar wind speed is higher (Wang et al, ; Wang, Xing, et al, ). This dawn‐dusk asymmetry is consistent with the DD‐related foreshock perturbations being produced on the side of quasi‐parallel shock, which is more often on the dawnside because of the Parker spiral IMF.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Such tailward propagation and the resulting magnetopause deformation have been observed in the dayside magnetosheath by using simultaneous measurements from two satellites (Sibeck et al, ). There have been two observational events from a single satellite showing HFA‐like perturbations in the midtail magnetosheath at X ~ −50 R E (Wang et al, ) and distant tail at X ~ −300 R E (Facskó et al, ). In these two events, no conjugate observations were available near the dayside bow shock to show their direct connection with foreshock perturbations; nevertheless, these tail perturbations have the HFA‐like features, suggesting that a foreshock‐originating perturbation may retain as it propagates further downtail and thus continues to affect the tail magnetopause.…”
Section: Introductionmentioning
confidence: 99%
“…A slight asymmetry in bulk GSE Y velocity is also visible on the dusk tail of Earth near 10 Re (Figure 7); how this connects to the SWD asymmetry is unclear. Future work evaluating SWD and FPI data in the context of IMF direction changes, and hot electron enhancements and other parameters could provide more clarity regarding this asymmetry (Kiehas et al., 2018; Wang et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Based on past statistical studies showing tailward, BBFs are more prominent on the dusk (+ Y ) side of the magnetotail, while Earthward flows are nearly symmetrically distributed or slightly more prominent on the dusk side (Kiehas et al., 2018), it is an unexpected result that the SWD counts are concentrated on the dawn (− Y ) side. ARTEMIS studies in the midtail magnetosheath have shown substantially higher fluxes for hot electron enhancements on the dawn side versus the dusk side, which could explain this asymmetry (Wang et al., 2015). Kiehas et al.…”
Section: Swd Case Study and Validationmentioning
confidence: 99%
“…Therefore, plasma transport across the distant magnetopause depends less on magnetic reconnection (as is the case at the dayside magnetopause; see Burch et al, ; Paschmann et al, , ) and more on large‐scale wave perturbations (Chen et al, ; Hasegawa et al, ). Accurate modeling of this transport, which can dominate solar wind plasma population of the distant tail, requires detailed investigation of the plasma characteristics around the nightside magnetopause (Artemyev et al, ; Wang et al, , ).…”
Section: Introductionmentioning
confidence: 99%